2015
DOI: 10.1177/1071100715576485
|View full text |Cite
|
Sign up to set email alerts
|

Functional Outcomes of Tibialis Posterior Tendoscopy With Comparison to Magnetic Resonance Imaging

Abstract: Level IV case series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 22 publications
(61 reference statements)
1
20
0
Order By: Relevance
“…Radiographs can be normal, although MRI may show PTT inflammation or early signs of degeneration. 49…”
Section: Stage Imentioning
confidence: 99%
See 1 more Smart Citation
“…Radiographs can be normal, although MRI may show PTT inflammation or early signs of degeneration. 49…”
Section: Stage Imentioning
confidence: 99%
“…Possible soft tissue procedures include tenosynovectomy, PTT repair, and tendon transfer. 49,90,112 Some surgeons believe that soft tissue procedures alone are insufficient and also recommend the addition of a medial calcaneal osteotomy, but this has not been studied for cases without deformity.…”
Section: Ptt Insufficiencymentioning
confidence: 99%
“…Bulstra et al (18) reported a symptomatic improvement with early mobilization of the joint in a series of 17 patients, of whom 2 required a second endoscopic intervention due to symptom relapse caused by adhesions that did not lead to progression of tibial dysfunction. Gianakos et al (19) also reported relapse of symptoms, but with no evidence of progression of tendon dysfunction. In our series, only one patient complained of persistent pain that lasted for 3 months and was resolved after physical therapy.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, PTT tenography and local anaesthetic tendon sheath injections were described as reliable diagnostic tools (Cooper et al 2007; Jaffee et al 2001). Recently, the use of tendoscopy has yielded diagnostic advantages for early recognition of PTT dysfunction (Gianakos et al 2015). …”
Section: Discussionmentioning
confidence: 99%